Attention bias for sleep-related stimuli in primary insomnia and delayed sleep phase syndrome using the dot-probe task. - MacMahon, K; Broomfield, N; Espie, C (2006)
STUDY OBJECTIVES: Cognitive models of primary insomnia (PI) suggest attention bias as a maintaining process. This study used a hallmark measure of attention bias, the dot-probe task, to determine whether attention bias to sleep-related stimuli is present in individuals with PI. Control groups of good sleepers (GS) and individuals with delayed sleep phase syndrome (DSPS), a sleep disorder with no presumed cognitive pathway and, hence, no predicted association with attention bias, were included. DESIGN: A between-groups (PI, DSPS, GS) design was employed. Participants completed a dot-probe task with stimuli comprising sleep-related and neutral words, balanced for length and frequency of usage. It was predicted a priori that PI would show greater attention bias to sleep stimuli compared with GS and DSPS groups. No difference between GS and DSPS was predicted. PARTICIPANTS: Sixty-three individuals completed the study (PI = 21; DSPS = 22; GS = 20), with those in PI and DSPS classified by International Classification of Sleep Disorders criteria according to self-report sleep diaries and actigraphy. GS scored < 5 on the Pittsburgh Sleep Quality Index, reported being good sleepers, and met no criteria for a current or previous sleep disorder. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: As predicted, PI showed increased vigilance for sleep-related stimuli relative to GS and DSPS. No differences between GS and those with DSPS were found. The PI group showed shorter response latencies relative to the GS and DSPS groups. CONCLUSIONS: Results support an association between attention bias and PI. Further work must determine whether or not attention bias is a causal factor. Speeded responses in the PI group suggest heightened arousal, indicating that physiologic factors may play a related role.